PELES PEDAGÓGICAS (Revista Apotheke, 2022)
Presenting the sensory book Pedagogic Skins (2010) compound as a tissue showcase this article becomes a way to think about creative processes and reveal the life of one artist, researcher and teacher present in it. The "skin-metaphors" were produced with materials, textures, colors, shapes, words and percentages, such as tissue-metaphor provoke further lecture.
Keywords: Art; teaching; research; metaphor